Remimazolam and propofol combination in ischemic cerebrovascular disease endovascular treatment: a randomized study - Tianxiao Liu; Liyin Qin; Maolin Su; Yunting Wei; Huabo Yu; Hao Wei; Yubo Xie; Jing Chen (Scientific Reports)
Abstract The choice of general anesthetic drugs is crucial. We aimed to investigate the effects of different doses of remimazolam combined with propofol in patients with ischemic cerebrovascular disease. A total of 105 patients were selected and divided into three groups by the random number table method (n = 35), group P, group R1, and group R2. Group P received a continuous propofol infusion. In contrast, Group R1 and Group R2 received continuous infusion of 0.1 mg/kg∙h and 0.2 mg/kg∙h of remimazolam, respectively, combined with propofol. MAP, HR, and BIS, extubation time, and 30-day postoperative mortality rate were recorded. Neurocognitive function and neurofunctional outcomes were followed up 1 day before, 1, 3, 7, 30, 90, and 180 days after. Compared with group P, the incidence of intraoperative hypotension in group R1 was lower, the fluctuation of mean blood pressure (ΔMAP) was decreased, the intraoperative dosage of propofol and ephedrine was decreased, the recovery time and extubation time were shortened, and the CAM-CR score on the 1st and 7th day after surgery was reduced. Compared with the R1 group, the incidence of intraoperative hypotension in group R2 was increased, the ΔMAP was increased, and the recovery time and extubation time were shortened. Remimazolam combined with propofol general anesthesia for interventional treatment of ischemic cerebrovascular disease can achieve satisfactory sedation depth, fewer adverse reactions, and does not affect patients’ postoperative neurocognitive function recovery and neurological function outcome. Compared with propofol alone, the hemodynamics of group R1 are more stable, and the recovery of group R2 is faster. Remimazolam may have a potential brain protective effect in Patients undergoing endovascular treatment for ischemic cerebrovascular disease.